Hypertrophic Cardiomyopathy Cardiac Troponin C Mutations Differentially Affect Slow Skeletal and Cardiac Muscle Regulation - Veltri, Tiago; Landim-Vieira, Maicon; Parvatiyar, Michelle S.; Gonzalez-Martinez, David; Dieseldorff Jones, Karissa M.; Michell, Clara A.; Dweck, David; Landstrom, Andrew P.; Chase, P. Bryant; Pinto, Jose R. (Frontiers in Physiology, 2017)
Mutations in TNNC1—the gene encoding cardiac troponin C (cTnC)—that have been associated with hypertrophic cardiomyopathy (HCM) and cardiac dysfunction may also affect Ca2+-regulation and function of slow skeletal muscle since the same gene is expressed in both cardiac and slow skeletal muscle. Therefore, we reconstituted rabbit soleus fibers and bovine masseter myofibrils with mutant cTnCs (A8V, C84Y, E134D and D145E) associated with HCM to investigate their effects on contractile force and ATPase rates, respectively. Previously, we showed that these HCM cTnC mutants, except for E134D, increased the Ca2+ sensitivity of force development in cardiac preparations. In the current study, an increase in Ca2+ sensitivity of isometric force was only observed for the C84Y mutant when reconstituted in soleus fibers. Incorporation of cTnC C84Y in bovine masseter myofibrils reduced the ATPase activity at saturating [Ca2+], whereas, incorporation of cTnC D145E increased the ATPase activity at inhibiting and saturating [Ca2+]. We also tested whether reconstitution of cardiac fibers with troponin complexes containing the cTnC mutants and slow skeletal troponin I (ssTnI) could emulate the slow skeletal functional phenotype. Reconstitution of cardiac fibers with troponin complexes containing ssTnI attenuated the Ca2+ sensitization of isometric force when cTnC A8V and D145E were present; however, it was enhanced for C84Y. In summary, although the A8V and D145E mutants are present in both muscle types, their functional phenotype is more prominent in cardiac muscle than in slow skeletal muscle, which has implications for the protein-protein interactions within the troponin complex. The C84Y mutant warrants further investigation since it drastically alters the properties of both muscle types and may account for the earlier clinical onset in the proband.